Hubungan Antara Pengetahuan Dengan Keaktifan Di Posyandu LansiaDesa Klaseman Kecamatan Gatak Kabupaten Sukoharjo Tahun 2016 - Tri Prihantoro, Chahya; Bejo Raharjo, SKM, M.Kes, SKM.,M.Kes; Anisa Catur Wijayanti,, SKM., MEpid (2016)
Benefits of posyandu activity of elderly is to get health and their healthy controlled. However, monthly elderly posyandu is not always attended by the elderly. The knowledge factor of the elderly is an important one that might affect them to take part in the posyandu actively . Their lack of knowledge can result in their inactiveness to take part in the posyandu. The Objective study of this research is to know the relation between elderly people's knowledge with theiractive participation to take part inPosyandu Klaseman village in Gatak sub-district, Sukoharjo Regency. This study is quantitative. The Research methods used are analytical observative and cross sectional study approach. The sample research are 146 elderly as member of elderly posyandu at Klaseman village with taking sample using cluster random sampling. Instrument research used are knowledge questionnaires about posyandu and their active participation taken from presence book for the last 6 month. Data are analyzed using Chi-square test. Result of study is 104 respondents (71,23%), with good knowledge, 85 respondents (58,22%) actively following elderly posyandu. Results of statistic can be concluded that there is a relation between elderly people's knowledge with their active participation in Posyandu Klaseman, Gatak sub district, Sukoharjo Regency in 2016. (p value= 0,006; PR= 2,778; 95% CI= 1,330-5,803).